Tinjauan Yuridis Tindak Pidana Pornografi dan Penerapan Prinsip Right to be Forgotten di Indonesia - Arini Ferya Putri; Tantimin Tantimin (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
This study analyzes the crime of cyber pornography in the Indonesian legal system and the position of the rights of victims of cyber pornography in terms of the principle of rights to be forgotten. The method used is normative legal research that is prescriptive and applied, analyzing secondary data in the form of primary legal materials and secondary legal materials. Obtaining data using library research techniques and analyzed using the syllogism method with a deductive pattern. This study shows that pornography has complex legal arrangements in Indonesia, but cyber pornography does not yet have comprehensive regulations. An understanding of the position of the victim of the right to be forgotten in the case of cyber pornography can be based on the provisions of Article 26 of the ITE Law.